Oberonia mahaeliyensis (Orchidaceae: Epidendroideae: Malaxideae), a new species from montane cloud forest of Sri Lanka - Bandara, Champika; Lakkana, Tithira; Ediriweera, Sisira (Phytotaxa, 2022)
Oberonia mahaeliyensis C. Bandara, Lakkana, Ediriweera sp. nov. is described and illustrated in montane cloud forests of Sri Lanka. Complete taxonomic description, color photographs and line drawings of the species are provided in this account.